2022
DOI: 10.1177/10778004221079409
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of One Book About Friendship in the Lives of Readers

Abstract: Research shows the benefits quality friendships have throughout humans’ lives. Recent scientific literature focuses on social impact. However, the social impact of reading and dialoguing about a book about friendship is not explored. This study aims to analyze the impact of “Creative Friendships” in the lives of participants and their surroundings. Using communicative methodology, based on dialogical co-creation from the start, it includes 30 participants from diverse backgrounds and ages through individual in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Research has shown that the key to a healthy and happy life relies on quality relationships (Gómez et al, 2022 ; Mineo, 2017 ). Indeed, there is a wealth of scientific literature on the impact of strong social relationships and friendships on wellbeing and health, both physical and mental (Bosle et al, 2022 ; Gan & Best, 2021 ; Glaser et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the key to a healthy and happy life relies on quality relationships (Gómez et al, 2022 ; Mineo, 2017 ). Indeed, there is a wealth of scientific literature on the impact of strong social relationships and friendships on wellbeing and health, both physical and mental (Bosle et al, 2022 ; Gan & Best, 2021 ; Glaser et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%